COMPARATIVE LEGAL STUDIES ON WOMEN'S RIGHTS IN THE GULF COUNTRIES: RELEVANCE AND IMPORTANCE TO GLOBAL AND UKRAINIAN LEGAL DISCOURSES - Alla Taylor (Scientific Journal of Polonia University, 2025)
This article is highlighting the critical role of comparative legal studies in understanding women's rights in the Persian Gulf region and their broader implications for international legal discourses. The study aims to explore how legal systems in these states navigate the complexities of domestic traditions, Islamic principles, and international human rights obligations. By analyzing key developments and challenges, the paper highlights the broader implications of these legal reforms for international legal science and provides insights applicable to other national contexts, including Ukraine. For the research comparative and analytical methods were used, focusing on regional legal systems and their evolution in addressing gender equality. Methods used include analysis and synthesis to evaluate legal frameworks, comparative techniques to identify similarities and differences among Gulf Cooperation Council (GCC) states, and contextual analysis to assess the interaction between local customs and global norms. Key findings include the identification of gradual, culturally sensitive approaches to reform that align domestic laws with international standards. The paper also discusses the relevance of these findings for Ukraine, emphasizing the importance of balancing traditional values with human rights commitments. By bridging regional specificities and international principles, this article contributes to a deeper understanding of women's rights and the global challenges of harmonizing legal frameworks with evolving societal needs.